(untitled) (Mustansiria Dental Journal, 2004)
Many bone replacing materials had been used to manage the problem of large defect folowing oralsurgery, of these materials include hydroxyapatite, bone morphogenic protein, allograft. nI this experimental study a pastes of eggshel powders and calcium sulfate (callus) had been implanted ni holes created ni the mandible of the six dogs and compared with control holes that filled nothing The results were evaluated clinically, radiographically and histopathologically. Clinically at the 7 postoperative day showed that the hole that filled with the cgg shell completely healed and difficult ot distinguish from het adjacent normal bone. While the hole that filed with calcium sulfate also proved a good healing potential but at less degree from that of eggshell, whereas the control hole was clearly obvious. Radiographically Osteogenesis was assessed by the degree of opacities ni that seems ot be clear in the three holes, which made on the mandible (Control, and the treated groups). But seem to be complete opacity ni the two treated group, while the control group only seems to be little. Histopathologically The results showed heavy infiltration of active osteoblasts cells which appear as a sheet of primitive spindle shaped cells surrounding the eggshell materials with immature bone (osteoid) along ti In control hole no osteoblast cell is seen only fibrosis. The hole that filled with callus showed moderate bone activity with little amount of osteoblast cells when compared with egg shel.